2013
DOI: 10.1177/0969141313499147
|View full text |Cite
|
Sign up to set email alerts
|

The effect of false positive breast screening examinations on subsequent attendance: retrospective cohort study

Abstract: Objectives To investigate the effect of false positive breast screening examination results on subsequent attendance in the UK National Health Service Breast Screening Programme. Methods 253,017 previously screened women who were invited for rescreening were studied. Attendance rates of women who had received a normal result at the last (index) screen were compared with those of women who had received a false positive result. The effects of age, type of index screening examination ( prevalent or incident) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…In their retrospective cohort study of 253,017 women, they found that women with a false-positive mammogram were more likely to return for subsequent screening than those who had normal screening, 87.7% versus 86.0%. 52 …”
Section: False-positive Resultsmentioning
confidence: 97%
“…In their retrospective cohort study of 253,017 women, they found that women with a false-positive mammogram were more likely to return for subsequent screening than those who had normal screening, 87.7% versus 86.0%. 52 …”
Section: False-positive Resultsmentioning
confidence: 97%
“…This is of concern as more frequent screening results in higher cumulative false positive findings, 26 which in turn increases the risk of invasive procedures and, based on our study and others, 6 lowers screening retention. In addition, modeling studies show that biennial screening does not lead to higher prevalence of latestage breast cancer than annual screening.…”
Section: Discussionmentioning
confidence: 98%
“…10 A recent study in the United Kingdom showed that while the retention rate was not affected by false positives, it was reduced in women who underwent biopsies. 6 Two studies in Canada, both published over a decade ago, found that false positive screening results reduced the likelihood of screening retention. 11,12 There are important differences in the organization and delivery of screening programs and in the characteristics of the populations screened across different countries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Biennial screening from age 50 to 74 years is projected to cause approximately one-fifth of the radiationinduced breast cancer cases caused by annual screening beginning at age 40 years. In one study, pathologists disagreed about the diagnosis of invasive breast cancer in 11% of cases (95% CI, [8][9][10][11][12][13][14][15][16] and about the diagnosis of ductal carcinoma in situ in 21% of cases (95% CI, 19-24). 5 The model estimates that annual screening of 100,000 women from age 40 to 74 years will avert 928 breast cancer deaths.…”
mentioning
confidence: 99%